Development and pasteurization of in-packaged ready-to-eat rice products prepared with novel microwave-assisted induction heating (MAIH) technology - Yi-Chen Lee; Chiu-Chu Hwang; Yung-Hsiang Tsai; Yi-Ting Huang (Applied Food Research)
The soaked white rice samples were subjected to microwave-assisted induction heating (MAIH) system consisting of a microwave heating unit (power = 1000 W, frequency: 2450 MHz) in the upper part and an induction unit (power = 1500 W) in the lower part at two set temperatures (120°C and 100°C) for different heating times. The aerobic plate count (APC), lightness (L*), redness (a*), yellowness (b*), whiteness (W), and hardness of the rice samples decreased significantly with prolonged heating, whereas the adhesiveness, cohesiveness, chewiness, moisture content, and water activity increased with increasing heating time. The rice samples subjected to MAIH at 120°C for 240 s or at 100 °C for 300 s had transparent cores with an absence of fine particles, indicating that the rice samples were fully cooked. The relevant microbial counts were below the detectable levels, and the preset target temperature could be attained at the maximum temperature of the rice samples. In addition, it is known from the temperature profile that the thermal lethality (F90°C) of MAIH 120°C for 240 s and MAIH 100°C for 300 s is 935 min and 14.1 min, respectively, which has exceeded the 6D value reduction requirements for the target microorganism non-proteolytic C. botulinum. (F90°C =10.0 min). In general, the optimum heating conditions for obtaining MAIH-prepared rice with color, texture, and sensory qualities similar to those of traditionally steamed rice were: heating at 120°C for 240 s or 100°C for 300 s. This study is the first to employ MAIH for rapid preparation of pre-packaged ready-to-eat (RTE) rice products, with at least 80 % reduction of the heating time compared with that of traditional steaming.